2019
DOI: 10.1002/jcla.22872
|View full text |Cite
|
Sign up to set email alerts
|

IDO and intra‐tumoral neutrophils were independent prognostic factors for overall survival for hepatocellular carcinoma

Abstract: BackgroundBoth Indole‐amine‐2,3‐dioxygenase (IDO) and neutrophils were proved to have pro‐tumor effect in some kinds of solid tumors by immune suppression. However, little is known about their effect on hepatocellular carcinoma (HCC) and the relationship between these two immune‐suppressive factors. The aim of this study was to evaluate the prognostic significance of IDO and intra‐tumoral neutrophils and their correlations in HCC.MethodsSpecimens’ tissue microarray (TMA) for 153 HCC patients was used in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…In line with these findings, expression of AHR, together with IDO1, kynurenine, and PD-L1, correlated with poor prognosis in hepatocellular carcinoma patients [66]. Tissue microarray analysis of 153 HCC patients confirmed a negative correlation of IDO expression and overall survival [67]. Likewise, as a promoter of HCC proliferation and tumor invasion, TDO has also been suggested as a new prognostic biomarker of HCC [68].…”
Section: Ahr In Hepatocellular Carcinomasupporting
confidence: 54%
See 1 more Smart Citation
“…In line with these findings, expression of AHR, together with IDO1, kynurenine, and PD-L1, correlated with poor prognosis in hepatocellular carcinoma patients [66]. Tissue microarray analysis of 153 HCC patients confirmed a negative correlation of IDO expression and overall survival [67]. Likewise, as a promoter of HCC proliferation and tumor invasion, TDO has also been suggested as a new prognostic biomarker of HCC [68].…”
Section: Ahr In Hepatocellular Carcinomasupporting
confidence: 54%
“…(D) Alcohol-induced liver injury: AHR activation reduces EtOH-induced oxidative stress, inflammation, and hepatocyte apoptosis [49,50]. (E) HCC: increased production of the AHR ligand kynurenine via TDO and IDO1 results in upregulation of PD-L1, impaired CD8 T cell responses, and tumor progression [65][66][67][68]. (F) Fibrosis: AHRdependent IL-17 and IL-22 production as well as AHR activation via IDO2/Kyn can promote liver fibrosis [56,57], while ITE-induced AHR activation in HSCs dampens liver fibrosis [54].…”
Section: Discussionmentioning
confidence: 99%
“…Although significance of our approach is the identification of correlation pattern by combination analysis, such an approach at protein levels is laborious and often limited with the sensitivity to demonstrate correlation. Nevertheless, our results were supported by previous studies which demonstrated that some B7 family molecules such as PD-L1 ( 64 , 65 ), PD-L2 ( 66 ), PD-1 ( 67 ), B7-H2 ( 68 ), B7-H3 ( 69 ) and IDO ( 70 ) play a significant functional role in modulating anti-HCC immunity. Although we have demonstrated the synergistic functions of IDO and PD-L1, future studies are necessary to determine if the other identified correlation of costimulatory and coinhibitory molecules play a functional synergistic role in modulating anti-HCC immunity.…”
Section: Discussionsupporting
confidence: 90%
“…Several reports indicate that IDO-1 expression is increased in human cancer tissues and patient follow up studies reveal that IDO-1 expression is associated with patient outcome [67,68]. In a prospective study of hepatocellular cancer patients, tissue IDO expression is negatively associated with patient survival: a high IDO expression is an independent prognostic factor for poor overall survival [69]. Tumor TDO overexpression was reported to be associated with poor survival in patients with breast cancer [70] and hepatocellular cancer [71].…”
Section: Tryptophan Catabolic Enzymes As Prognostic Biomarkers Of Cancermentioning
confidence: 99%